Investigating the kinetics at low temperature heat pump drying and conventional drying of osmotic dehydrated blueberries - Hristo Hristov (EDP Sciences, 2021)
The possibilities for low-temperature heat pump and conventional drying of blueberries during preliminary osmotic dehydration was studied. A full factor experiment of type 22+3 was performed. The kinetics of the process during variation of the main mode parameters: inlet temperature and thickness of the drying layer (load on the scaffolding) was studied. The curves of the drying process U = f (τ) and the curves of the drying speed dU / dτ = f (U) were constructed. The influence of the regime parameters on the drying time was established. Regression models of the drying coefficient during the second period of drying were presented.